GIS Added Methdology for Mountain Land Evaluation - Poudel, Krishna Prasad (Himalayan Review, 2011)
Available with fulltext. Key words: GIS Methdology; Mountain Land; Altitude; Tempreture The Himalayan Review Vol. 24-28 1993-1997 Page: 1-8 Uploaded date: 15 June, 2011